Effects of fermentation and wrapping materials on nutritional and anti-nutritional properties of watermelon (Citrillus lanatus) seeds. - Akele, E O; Akinyosoye , F A; Oyetayo , V O (American Journal of Food Sciences and Nutrition, 2022)
Purpose: This study aimed at evaluating the effects of fermentation on minerals, anti-nutrients, and proximate properties of seeds of watermelon subjected to fermentation. Methodology: Three containers were used for the fermentation process viz: calabash, plastic, and foil paper. The dehulled, sorted and washed watermelon seed were boiled until soft and divided equally into the different containers and fermented for nine days. The mineral, proximate and anti-nutritional properties of the fermented samples were compared with ogiri samples purchased from the market. Findings: There was increase in protein values of the fermented samples as follows calabash (37.55%), foil paper (35.51%) and plastic (35.51%) compared to the sample bought from the market (35.30%) and with significant difference across samples at 95% confidence level. Samples fermented in plastic had the highest moisture content (13.89%) and there was a significant difference among other samples with the sample fermented in calabash had the least value (11.24%). The sample in foil had the highest value (26.85%) of fat while the sample bought from market have the least (25.72%). Potassium was highest in value ranging from 41.65mg/100g to 27.45mg/100g while cupper with values ranging from 0.30mg/100g to 0.08mg/100g was least across the samples. For anti-nutrients, flavonoid has the highest (2.20mg/100g) while alkaloid was the least in value (0.49mg/100g). Samples fermented had better results in terms of mineral, proximate and anti-nutritional properties as compared to sample bought from the market. Results from this study revealed that fermentation significantly increase the nutrient and reduce the anti-nutrient contents of water melon seeds. Results from this study revealed that this unconventional substrate may serve as alternative to melon and ugba seeds for the production of ogiri, an indiginous condiment. Recommendation: Watermelon seed as an unconventional substrate could be used as an alternative to oily seeds in the production of ogiri condiment, as well as a healthy and cheap source of protein. Conversion of watermelon seed to ogiri is a form of turning waste to wealth, thus creating job opportunities thereby reducing poverty.